Somatotypes of children in different areas of Indonesia - Ashizawa K, Rahmawati NT Hastuti J, Yevita N (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Human populations consist of individuals who differ widely in body shape and size. Somatotypesare morpho-phenotypic ranges along continua of variation, which possess constantly recognizablecharacteristics and are the functional end products of the whole genetic and the developmental complex.Objective: The objective of this cross-sectional study was to establish the somatotypes of urban, agriculturaland fishing village children in Indonesia.Method: Anthropometric somatotypes of children are considered in a cross-sectional sample of schoolgoing,ranging in age from 7-15 years. A total numbers 1716 (816 boys and 900 girls) consist of childrenin urban Yogyakarta (340 boys and 371 girls), agricultural Bantul (222 boys and 243 girls), and fishingPadang (254 boys and 286 girls). Heath-Carter somatotypes were determined for all subjects.Result: The Yogyakarta children were taller and heavier than their agricultural and fishing counterparts inboth sexes. The Yogyakarta children (urban) were more endomorphic, mesomorphic, and less ectomorphicthan the Bantul and Padang children. The Padang children (fishing village) were more ectomorphic and lessendomorphic than the Yogyakarta and Bantul children. The mean somatotype of boys and girls were 3.8 â3.6 â 3.7 and 4.2 â 3.1 â 3.6 (in urban city, respectively), 2.8 â 3.2 â 4.1 and 3.5 â 2.9 â 3.9 (in anagricultural village, respectively), and 2.5 â 3.5 â 3.8 and 3.5 â 3.1 â 3.5 (in fishing village, respectively).Conclusion: The finding indicated among the Indonesian children, the distribution of somatotype accordingto age was different between urban Yogyakarta, agricultural Bantul and fishing Padang. In general, thewell-off children were more endomorphic, and the low-income children were more ectomorphic.Key words: somatotype anthropometric â urban, agricultural, and fishing village children